Physico chemical and sedimant characteristics of the bottom sediment of Terengganu river, Terengganu, Malaysia - Jamil Tajam (Fakulti Sains dan Teknologi, 2011)
A comprehensive study on the geochemistry and sediment characteristics of the sediment of Terengganu River was carried out in order to understand the effects of development and the pollution status of the river. The factors investigated were salinity, temperature, pH, sedimentology, organic carbon, metal concentrations and sedimentation rate. Sampling activities were conducted from May, 2002 to April, 2003 during the non-monsoon and monsoon season. Studies were carried out at 40 stations along the Terengganu River investigating physical parameters, sedimentology, heavy metals, and organic carbon (OC). Two core samples were collected in order to determine sedimentation rates.